MULTIFUNCTIONAL ANALOG DEVICE BASED ON AMPLIFIERS WITH REGULATED GAIN - A. V. Guba; R. K. Gereykhanov; A. M. Magomedov (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In this article analog device capable to make portion of different functions in wide frequency band is discussed. Some recommendations for possible application examples are offered.